Establecimiento de las condiciones óptimas para la micropropagación por fases de clones promisorios de piñón (Jatropha curcas l.) del Instituto Nacional de Investigaciones Agropecuarias con fines de mejoramiento genético vía irradiación - Gordillo López, Emely Valentina (2020)
Piñón crop has expanded in recent years. However, the classical production system is not enough to cover the market demand. Currently, there are no commercial varieties or wild individuals with characteristics of interest in Ecuador. Previous studies have shown that a high percentage of the seeds obtained in the field are discarded due to their low germination level. There are other problems such as the low level of viability and non-uniform development of the seedlings. The present work proposes a partial solution to the aforementioned problems, from the study of the optimal conditions for the in vitro propagation by phases of promising pinion clones (Jatropha curcas L.). A protocol has been formulated for the establishment of clones from apical and axillary meristems. A Completely Random Design (DCA) with a 2 by 4 by 2 factorial arrangement was used. After four weeks of evaluation and using MIBJ-2 supplemented with IBA, Kn and adenine sulfate, the piñón was able to generate 2.2 shoots and its three true leaves on day 18. Additionally, a procedure for the multiplication of established shoots of promising clones was validated using a DCA with a factorial arrangement of 2 by 2 by 2 by 2. The MEBJ-2 culture medium supplemented with BAP and AIA showed the best results regarding its variables. In its best treatment, it generated increments of 0.64 centimeter in length and a total of 3.8 internodes per explant. Finally, for the rooting phase of explants, a DCA with a 2 by 4 factorial arrangement was used. After six weeks of evaluation, the EYM-1 supplemented with 0.2 mg-L of IBA, increased the length of the shoot 0.12 cm and generated rootlets of approximately 0.3 centimeter approximately.